Construire la lutte queer en Iran et dans la diaspora d'Iran. Entretien avec Saghi Ghahraman - Mahdis Sadeghipouya; Sahar Aurore Saeidnia (Genre, Sexualité et Société)
This interview examines the life of the queer poet and activist Saghi Ghahraman. She fled her native Iran after being arrested for working with a communist organization’s women’s branch. She has been living in exile in Canada for three decades and is devoted to providing a voice for the Iranian gay, lesbian, and trans community.